1983
DOI: 10.1159/000120139
|View full text |Cite
|
Sign up to set email alerts
|

Limberg-Latissimus Dorsi Myocutaneous Flap for Closure of Myelomeningocele

Abstract: A method is presented in which two well-recognized plastic surgical flap techniques are coupled: the Limberg rhomboid transposition flap and the latissimus dorsi myocutaneous flap. The technique was used in 2 patients to provide ample, innervated, and well-vascularized skin cover over myelomeningocele defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In this fashion, a sheet of muscle can then be flapped down over the entire defect and sewn in place with 2-0 vicryl. There are many reports of complex plastic surgical closures in the literature; 4,5,7,10 however, at our institution we have found that closures of even the largest defects ( Fig. 2) can be effectively performed by the neurosurgeon when using the above techniques.…”
mentioning
confidence: 67%
“…In this fashion, a sheet of muscle can then be flapped down over the entire defect and sewn in place with 2-0 vicryl. There are many reports of complex plastic surgical closures in the literature; 4,5,7,10 however, at our institution we have found that closures of even the largest defects ( Fig. 2) can be effectively performed by the neurosurgeon when using the above techniques.…”
mentioning
confidence: 67%
“…Various methods of skin closure following repair of large myelomeningocel have been utilized successfully, these include local skin flaps; lumbosacral rotation flap [6], Limberg flap [17,19], transposition flap [4,10], double Z rhomboid flaps [5], bilateral bipedicled flaps [9], musculocutaneous flap variations, latissimus dorsi advancement flaps without lateral incisions [13], reverse latissimus dorsi flap [23,24], distally based latissimus dorsi flap [22], latissimus dorsi bipedicled and relaxing incision with superficial gluteal fascia [16], compound latissimus-gluteus flaps without a relaxing incision [7,14,21], primary skin grafting on turnover muscle and delayed grafting have also been used [ 11 ]. Local skin flaps require extensive skin undermining and thus there is a greater risk of wound edge necrosis than with muscle flaps.…”
Section: Discussionmentioning
confidence: 99%
“…They relied on a layer-by-layer closure of the dura and the junctional zone to prevent CSF leak. In addition, various skin flaps and myocutaneous flaps have also been designed to cover large defects [5,6,11].…”
Section: Discussionmentioning
confidence: 99%